The Determinant of Equity Share Price and the Listed Deposit Money Banks in Nigeria - Oyedokun, Godwin Emmanuel; Arotolu, Olusegun Adebowale; Vincent, Harison (JASF: Journal of Accounting and Strategic Finance, 2019)
In this study, the researcher examined the financial variables influencing the share price of listed deposit money banks in Nigeria. An ex-post facto research design was employed with the population consisting of all fifteen (15) listed deposit money banks on the Nigeria Stock Exchange (NSE), and a sample of twelve (12) listed deposit money banks on NSE was taken using filter criteria and judgmental sampling techniques. Secondary data used were sourced from the annual reports of the sampled banks and GTI Securities Ltd. for five years period from 2013-2017. Ordinary Least Square (OLS) was used to analyze the data. The results of the multiple regression revealed that the dividend payout ratio and price-earnings ratio have a significant positive relationship with the share price. The results also showed that dividend yield has a significant negative association with share price; the book value per share has no meaningful relationship with the share price. This study recommends that the shareholders in the deposit money banks should be guided by industry financial ratios, especially the profitability measures of price-earnings ratio and dividend payout ratio, as they are critical factors in predicting share price behavior.